Violación de la garantía constitucional en cuanto al plazo establecido en el procedimiento directo en los delitos flagrantes - Salazar Romero, Katy Maribel (2016)
Today we face a current to conclude the criminal process more quickly, under the circumstances of high crime that carries these days in addition to the saturation of the laws, to create new offenses every day and also increasing the work of judges and each day the number of prisoners without trial is increasing crowding prisons and prison without a conviction. That is why the negotiation of guilt is simply utilitarian since its purpose is to contribute to judicial decongestion, to achieve a state efficiency in the civil service (early administration) and enforce justice more effectively and reintegrating society to people who can be rehabilitated in a more useful way to keeping them in prison without a conviction. The present research is a deepening of one of the alternative mechanisms of conflict, such as the summary procedure in our legislation, which is provided in the Constitution of the Republic of Ecuador and in the Código Orgánico Integral Penal, treating of attaining a consistent and fair application of the rule and allow due process and fair, as well as direct procedure laid down in Article 640 of the Código Orgánico Integral Penal